MINDhEARTH: a school-based intervention to improve personal well-being, mindfulness and connectedness to nature in adolescents - Scafuto, Francesca; Conversano, Ciro; Presaghi, Fabio; Santoni, Giulia; Vaglini, Ilaria; Girardi, Francesco; Matiz, Alessio; Crescentini, Cristiano (Frontiers in Psychology, 2025)
The study evaluates the effectiveness of a novel program, called MINDhEARTH, grounded in the ecopsychological approach, and aimed to improve individual wellbeing and ecological self-awareness in adolescents. A pre- and post-intervention design involved 211 students from two Italian high schools, measuring Wellbeing through the Italian version of the Subjective Happiness Scale and Psychological Wellbeing Scale (PWB), Mindfulness through the short-form of Five-Facets Mindfulness Questionnaire and Nature Connectedness through the Italian version of Connectedness to Nature Scale. The questionnaire also included open-ended questions aimed at evaluating qualitative perception of personal benefits from the program. Multilevel regression analysis showed significant effect of intervention by time interaction on Subjective Happiness and on Autonomy, PWB subdimension. Among the facets of Mindfulness, results showed a significant effect for Acting with Awareness and a marginally significant effect for Non-reacting. Contrary to expectations, no significant interaction effect on Nature Connectedness was found. Nevertheless, qualitative reports through qualitative content analysis revealed connection to nature to be the second prevalent theme of perceived benefits, after connection with oneself. The study concludes with analysis of limitations and suggestions for future school mental health programs that consider a combination between mindfulness interventions and nature-based activities to increase wellbeing and antecedents of ecological citizenship.